Antioxidant Vitamin Supplementation Reduces Arterial Stiffness in Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 10 (6th August 2014) - Ashor, Ammar W.; Siervo, Mario; Lara, Jose; Oggioni, Clio; Mathers, John C.
Abstract: Background: Several studies tested the effects of supplementation with antioxidant vitamins on arterial stiffness, but the results were contradictory. Objectives: The aim of our study was to conduct a systematic review and meta-analysis investigating the effect of antioxidant vitamins on arterial stiffness and to determine whether the effects on arterial stiffness vary according to dose, duration of intervention, and health or nutritional status of the included participants. Methods: We searched 3 databases (Medline, Embase, and Scopus) for articles that potentially met the following eligibility criteria: 1 ) randomized controlled trials comparing antioxidant vitamins (vitamins C, E, and A and β-carotene) to either placebo or no active control in 2 ) adult participants aged ≥18 y; 3 ) antioxidant vitamins administered alone or in combination, irrespective of dose, duration, and route of administration; and 4 ) changes in arterial stiffness or arterial compliance. Data were pooled as standardized mean differences (SMDs) and analyzed using fixed- and random-effects models. Results: Data synthesis showed that antioxidant vitamins reduced arterial stiffness significantly (SMD: −0.17; 95% CI: −0.26, −0.08; P < 0.001). This effect was significant in experimental (SMD: −1.02; 95% CI: −1.54, −0.49; P < 0.001) and primary prevention (SMD: −0.14; 95% CI: −0.24, −0.04; P < 0.01) studies, whereas a trend for reduced arterial stiffness was observed in studies including participants with diseases (SMD: −0.19; 95% CI: −0.40, 0.02; P = 0.08). Vitamin supplementation improved arterial stiffness irrespective of age group and duration of intervention. Antioxidant vitamins were more effective in participants with low baseline plasma concentrations of vitamins C (SMD: −0.35; 95% CI: −0.62, −0.07; P < 0.016) and E (SMD: −0.79; 95% CI: −1.23, −0.33; P < 0.01). Conclusions: Supplementation with antioxidant vitamins has a small, protective effect on arterial stiffness. The effect may be augmented in those with lower baseline plasma vitamin E and C concentrations. This trial was registered at PROSPERO as CRD42014007260.